VEHICLE SCHEDULING IN A HARVEST SEASON - Gvozdenović, Nebojša; Brcanov, Dejan (Economics of Agriculture, 2018)
The collection of agricultural goods is a very dynamic process which involves the coordination of hundreds of transport routes and machines with respect the processing capacities at a factory. Numerous fluctuations in the number of transport vehicles, malfunctioning on engaged machines and weather conditions make the process of planning and maximizing the utilization of all resources very diffcult. In this paper we present a mathematical model and a heuristic algorithm that in a short period of time fnds nearly optimal solutions, which enables a dispatcher to re-plan and update the collection plan according to new constraints.